Pengaruh Lama Perkecambahan Terhadap Total Fenol, Flavonoid, Dan Aktivitas Antioksidan Tepung Kecambah Kacang Tunggak (Vigna unguiculata L. Walp.) - Putri, Amira; Wisaniyasa, Ni Wayan; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 1 (2021): Jurnal ITEPA, 2021)
This study aims to determine the effect of germination time on total phenolic content, total flavonoid content, and antioxidant activity of cowpea sprout flour, and to determine which germination time that will give the best result of total phenolic content, total flavonoid content, and antioxidant activity of cowpea sprout flour. The research design used in this study is Completely Randomized Design with five germination times such as 0, 12, 24, 36, and 48 hours with each treatment was repeated three times. The cowpea sprout flour was tested for total phenolic content, total flavonoid content, and antioxidant activity. The data obtained were analyzed by using Analysis of Variance (ANOVA), and if the treatment had significant effect followed by Duncan’s Multiple Range Test (DMRT). The result showed that germination of cowpea had a significant effect on total phenolic content, total flavonoid content, and antioxidant activity. The best germination time was 48 hours that resulted in total phenolic content of 256.16 mg GAE/100 g, total flavonoid content of 29.97 mg QE/100 g, and antioxidant activity (IC 50 ) of 5,928.39 mg/L.